2020
DOI: 10.31382/eqol.210603
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the effectiveness of the pick and roll offense at the 2017 European Men's Championship

Abstract: The evolution of basketball made the game faster, leading coaches to increase the use of pick and roll cooperation in offense. The purpose of this research was to investigate the performance time of the pick and roll every five minutes, the pair of players who participated in the pick and roll and the offensive action of the ball handler after the screen, in the European Men's Championship of 2017. The sample of the research was the sixteen games of the second round of the Championship. The instrument used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…Furthermore, most pick and rolls took place in the first quarter of each game (27.5 %). This finding is consistent with the results of Angelou et al (2021) and Gómez et al (2015) who found that most of the pick and roll actions were performed during that quarter (26.3% and 26.7% respectively). The reason that most pick and roll are performed in the 1st period may be the increased concentration of the players at the beginning of the match.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, most pick and rolls took place in the first quarter of each game (27.5 %). This finding is consistent with the results of Angelou et al (2021) and Gómez et al (2015) who found that most of the pick and roll actions were performed during that quarter (26.3% and 26.7% respectively). The reason that most pick and roll are performed in the 1st period may be the increased concentration of the players at the beginning of the match.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the execution time of the pick and roll in every five-minute span, most pick and rolls actions took place in the first five minutes of each quarter (53.2%), unlike the Men's European Championship, where most of the pick and roll actions were performed in the second five-minute span of each period (50.4%, Angelou et al 2021), but are consistent with the findings of Gómez et al (2015) who found that most pick and rolls were performed in the first five minutes of each period (51.2%). The interpretation of these findings needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations